Management of epidermolysis bullosa simplex in pregnancy: A case report - Nidhi Shah; Sangeeta Kumaraswami; Juliet E. Mushi (Elsevier, 2019)
Epidermolysis bullosa (EB) encompasses a group of diseases characterized by extreme fragility of skin and mucous membranes, resulting in blister formation following minimal injury. There are 4 types of EB, with epidermolysis bullosa simplex (EBS) being the most common. We report our experience with the care of a parturient woman diagnosed with EBS. There is little literature on pregnancy in women with this condition. Special precautions are necessary during diagnostic and therapeutic interventions to avoid bullae formation or exacerbation of existing lesions. Frictional or shearing forces are typically more damaging than compressive forces. Multidisciplinary planning was done for our patient to ensure uneventful labor and delivery. Elective induction of labor was started at 40 weeks of gestation. She eventually underwent a cesarean delivery after failed trial of labor. We present this case to highlight the obstetric and anesthetic implications of caring for a parturient with EBS. Keywords: Epidermolysis bullosa simplex, Bullae, Obstetric, Anesthetic, Parturient, Epidermolysis bullosa